Implementation of the Al-Miftah Method to Improve Students’ Ability to Read Turāth Books at Al-Masyad High School, Cijurai, Sukabumi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe the implementation of the Al-Miftah method in improving the mastery of reading traditional Islamic texts at Al-Mashhad Senior High School in Cijurai, Sukabumi. This study uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, in-depth interviews, and documentation of Al-Miftah teachers, students, and related parties. The results of the study indicate that the Al-Miftah method is implemented through the stages of introducing the basic rules of nahwu-sharaf, practicing reading traditional Islamic texts in stages, and strengthening understanding through repetition and direct practice. The implementation of this method has been proven to help students understand the structure of Arabic and improve their ability to read traditional Islamic texts, although several obstacles were still encountered, such as differences in students' Arabic language backgrounds, limited learning time, minimal independent practice, and limited mastery of the method by teachers. Efforts made to overcome these obstacles include learning grouping, time optimization, out-of-class practice assistance, and improving teacher competency through continuous training and evaluation. Thus, the Al-Miftah method has a positive contribution in increasing mastery of reading traditional books at Al-Mashhad Cijurai Sukabumi High School if supported by appropriate and continuous learning strategies